Enhancement of the Repair of Dog Alveolar Cleft by an Autologous Iliac Bone, Bone Marrow–Derived Mesenchymal Stem Cell, and Platelet-Rich Fibrin Mixture. Issue 5 (May 2015) - Yuanzheng, Chen; Yan, Gao; Ting, Li; Yanjie, Fu; Peng, Wu; Nan, Bai
<x xml:space="preserve">Abstract</x> Background: Autologous bone graft has been regarded as the criterion standard for the repair of alveolar cleft. However, the most prominent issue in alveolar cleft treatment is the high absorption rate of the bone graft. The authors' objective was to investigate the effects of an autologous iliac bone, bone marrow–derived mesenchymal stem cell, and platelet-rich fibrin mixture on the repair of dog alveolar cleft. Methods: Twenty beagle dogs with unilateral alveolar clefts created by surgery were divided randomly into four groups: group A underwent repair with an autologous iliac bone, bone marrow–derived mesenchymal stem cell, and platelet-rich fibrin mixture; group B underwent repair with autologous iliac bone and bone marrow–derived mesenchymal stem cells; group C underwent repair with autologous iliac bone and platelet-rich fibrin; and group D underwent repair with autologous iliac bone as the control. One day and 6 months after transplantation, the transplant volumes and bone mineral density were assessed by quantitative computed tomography. All of the transplants were harvested for hematoxylin and eosin staining 6 months later. Results: Bone marrow–derived mesenchymal stem cells and platelet-rich fibrin transplants formed the greatest amounts of new bone among the four groups. The new bone formed an extensive union with the underlying maxilla in groups A, B, and C. Transplants with the bone marrow–derived mesenchymal stem cells, platelet-rich fibrin, and their mixture retained the majority of their initial volume, whereas the transplants in the control group showed the highest absorption rate. Bone mineral density of transplants with the bone marrow–derived mesenchymal stem cells, platelet-rich fibrin, and their mixture 6 months later was significantly higher than in the control group (p < 0.05), and was the highest in bone marrow–derived mesenchymal stem cells and platelet-rich fibrin mixed transplants. Hematoxylin and eosin staining showed that the structure of new bones formed the best in group A. Conclusion: Both bone marrow–derived mesenchymal stem cells and platelet-rich fibrin are capable of improving the repair of dog alveolar cleft, and the mixture of them is more potent than each one of them used singly for enhancing new bone regeneration.